Pedagogical Stylistic Research: A Bibliometric Analysis using Vosviewer and Biblioshiny R From 2013-2023 - Dienana, Arina; Rizqia, Ana Sabila; Sopian, Asep; Abdullah, Muhammad Yahya (Tamaddun Life, 2024)
The aims of this research is to find out the dynamics relevant to pedagogical stylistic over period of ten years from 2013 until 2023 by analyzing research trends, citation trends, gap research and countries that have cooperative relations on pedagogical stylistic topic. Furthermore, the research method used bibliometric visualization and bibliometric analysis. Research data were extracted from a scopus database then analyzed with VosViewers applications and Biblioshiny R as data analysis software. The research stages included identification, eligibility assessment and inclusion screening which resulted in final data of 97 publications. The result indicate a rise in publications concern to pedagogical stylistic has increased, particularly in 2022. Publications from 2016 have the highest g-index and h-index scores among all years, with 76 citations, the citation trend for pedagogical stylistic happened in 2016. Russian, United kingdom and United State become a countries that have significant influence of this research. The most popular keyword were student, professional aspects, pedagogical stylistic and stylistic analysis.